EMPLOYEE PERFORMANCE TRANSFORMATION THROUGH COMPETENCE AND WORK ENVIRONMENT: THE MEDIATING ROLE OF WORK COMMITMENT AMONG SUMENEP REGENCY DPRD EMPLOYEES - Hertin Khalifatun Nisa Arifah; Muhlisin; Nurul Hidayat; Jannatul Firdaus; Hanifah Fauziyah; Syamsul Rizal; As'adi Khas (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effect of competence and work environment on employee performance with work commitment as a mediating variable at the Secretariat of the Regional House of Representatives (DPRD) of Sumenep Regency. The research employs a quantitative approach using Structural Equation Modeling (SEM) and SmartPLS analysis based on questionnaire data collected from employees. The findings indicate that competence does not significantly affect employee performance, while the work environment has a positive and significant effect. Work commitment also influences performance, but the negative relationship suggests that some employees work out of obligation rather than emotional attachment to the organization. Furthermore, competence and work environment affect work commitment, which acts as a mediating variable. The study concludes that improving employee performance requires not only strengthening technical competence but also fostering a supportive work environment and affective commitment. Therefore, the Secretariat of DPRD Sumenep is recommended to develop a more open work system, provide performance-based recognition, and create a comfortable and collaborative work environment.